2012
DOI: 10.1063/1.4760262
|View full text |Cite
|
Sign up to set email alerts
|

Magnetocaloric properties of La(Fe,Si)13-based material and its hydride prepared by industrial mischmetal

Abstract: Here, we choose La-Ce-Pr-Nd industrial mischmetal with low purity as raw material to prepare La(Fe,Si)13-based magnetocaloric material and its hydride. It is demonstrated that the introduced impurities in the starting materials do not impair the formation of NaZn13-type structure. The multi-replacement of La by magnetic atoms Ce,Pr,Nd enhances Curie temperature TC while keeps the strong itinerant electron metamagnetic behavior. As a result, good magnetocaloric (MCE) properties appear in La0.7(Ce,Pr,Nd)0.3Fe11.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(12 citation statements)
references
References 25 publications
0
12
0
Order By: Relevance
“…The change is comparative with the largest changes reported in the literature, indicating that it has a high hydrogen capacity, confirmed by the measured value of 1.71 per formula unit. Figure 1 (a) TC dependence on lattice constants (1:13 phase) for the samples (listed in Table 1) in response to various extents of hydriding, and (b) and (c) the same data with various La(Fe,Si)13-based samples reported in other studies included [30][31][32][33][34]36]. For each material, the non-hydrided base, partially and fully hydrided compounds are designated by open, partially filled and closed symbols, respectively.…”
Section: Two Vital Considerations Towards the Implementation Of Magnementioning
confidence: 79%
“…The change is comparative with the largest changes reported in the literature, indicating that it has a high hydrogen capacity, confirmed by the measured value of 1.71 per formula unit. Figure 1 (a) TC dependence on lattice constants (1:13 phase) for the samples (listed in Table 1) in response to various extents of hydriding, and (b) and (c) the same data with various La(Fe,Si)13-based samples reported in other studies included [30][31][32][33][34]36]. For each material, the non-hydrided base, partially and fully hydrided compounds are designated by open, partially filled and closed symbols, respectively.…”
Section: Two Vital Considerations Towards the Implementation Of Magnementioning
confidence: 79%
“…This is in accordance with reports on the appearance of a temperature hysteresis of the magnetization in similar materials. 15 While desirable, a quantitative analysis and elaborate theory is beyond the scope of the present paper.…”
Section: @T @Hmentioning
confidence: 98%
“…It is well known that the T C of LaFe 13Àx Si x (1.2 x 1.6) alloys, changing from 175 K for x ¼ 1.2e199 K for x ¼ 1.6, is far from room temperature [3e6]. In order to adjust the T C of LaFe 13Àx Si x alloys, a great deal of effort has been done, such as substituting Fe with Mn [7,8], Co [9] or Cr [10], substituting La with Ce [11], Pr [12] or Ca [13] and adding interstitial atoms H [14,15], C [16,17] or B [18,19]. It has been reported that the introducing of interstitial H atoms is the most efficient method to improve the T C to near room temperature as well as to keep the large magnetocaloric effect [20,21].…”
Section: Introductionmentioning
confidence: 99%